Pengaruh Layanan Penguasaan Konten Teknik Modeling Terhadap Resiliensi Akademik Siswa Pada Sekolah Menengah Pertama - Mella Maharani; Asih Menanti (INDONESIAN COUNSELING AND PSYCHOLOGY, 2022)
AbstractThis study aims to determine the effect of modeling technique content mastery services on the academic resilience of students at Amir Hamzah Medan Private Junior High School Period 2021/2022.  The method used in this study is a quantitative method.  This type of research is a quasi-experimental with a pre-test-post-test group design.  The subjects in this study were 22 grade VIII students who had low resilience.  The research data were collected with an academic resilience scale totaling 40 statement items that were valid and reliable.  Instruments are given before and after the implementation of content services.  The data were analyzed using the Wilcoxon test to see if there was a significant effect of providing modeling technique content mastery services on students’ academic resilience.  This can be obtained from the calculation results with the initial test score (pre-test) in the experimental group obtained an average = 109.4 while the post-test data obtained an average = 135.4.  This can be obtained from the Wilcoxon test which shows that the Wilcoxon level test is obtained Jcount = 115 while Jtable = 66. From the critical table J for the Wilcoxon marked level test for n = 22, = 0.05 according to the criteria for acceptance and rejection of the hypothesis, the hypothesis  accepted if Jcount > J table where 115 > 66, from this calculation it can be seen that the treatment in the experimental group means that the hypothesis is accepted.  This shows that there is an influence of modeling technique content mastery services on students’ academic resilience at Amir Hamzah Medan Private Junior High School. Period. 2021/2022.